Response of the equatorial ionosphere to the geomagnetic DP 2 current system. Issue 14 (25th July 2016) - Yizengaw, E.; Moldwin, M. B.; Zesta, E.; Magoun, M.; Pradipta, R.; Biouele, C. M.; Rabiu, A. B.; Obrou, O. K.; Bamba, Z.; de Paula, E. R.
Abstract: The response of equatorial ionosphere to the magnetospheric origin DP 2 current system fluctuations is examined using ground‐based multiinstrument observations. The interaction between the solar wind and magnetosphere generates a convection electric field that can penetrate to the ionosphere and cause the DP 2 current system. The quasiperiodic DP 2 current system, which fluctuates coherently with fluctuations of the interplanetary magnetic field (IMF) Bz, penetrates nearly instantaneously to the dayside equatorial region at all longitudes and modulates the electrodynamics that governs the equatorial density distributions. In this paper, using magnetometers at high and equatorial latitudes, we demonstrate that the quasiperiodic DP 2 current system penetrates to the equator and causes the dayside equatorial electrojet (EEJ) and the independently measured ionospheric drift velocity to fluctuate coherently with the high‐latitude DP 2 current as well as with the IMF Bz component. At the same time, radar observations show that the ionospheric density layers move up and down, causing the density to fluctuate up and down coherently with the EEJ and IMF Bz . Key Points: The solar wind‐magnetosphere interaction generates DP 2 current fluctuation The DP 2 current fluctuations penetrate to the equator and cause the equatorial electrodynamics to fluctuate It also causes the equatorial density to fluctuate which might affect the communication and navigation systems